SLANG WORDS IN GROWN UPS 2 MOVIE - Herman, Herman; Asanti, Chris; Setyowati, Ririn (Fakultas Ilmu Budaya Universitas Mulawarman, 2022)
ABSTRACTThis research aimed to identify the types of slang used by the characters and explain the function of slang uttered by the characters in Grown Ups 2 movie. This research employed a qualitative descriptive approach. The data source of this research was the script of Grown Ups 2 movie. The data were taken from the utterances, words, and conversation which contained slang words or phrases uttered by the four main characters. Through the findings of the analysis, there were 30 utterances containing the types of slang words. From four types of slangs that were fresh and creative, compounding, imitative, acronym and clipping, the four characters within the movie used only four types of slang, namely fresh and creative, compounding, imitative, and clipping. In types of slang, it was found that the characters had purposes when using those slangs word. It was revealed that there were three functions of slang, pursuit of self-identity, emotive feeling of slang users, and achieving politeness.Keywords: sociolinguistics, language variety, slang word ABSTRAKPenelitian ini bertujuan untuk mengidentifikasi jenis bahasa slang yang digunakan oleh para karakter dan menjelaskan fungsi bahasa slang yang diucapkan oleh para karakter dalam film Grown Ups 2. Penelitian ini menggunakan pendekatan deskriptif kualitatif. Sumber data penelitian ini adalah naskah film Grown Ups 2. Data diambil dari ujaran, kata, dan percakapan yang mengandung kata atau frasa slang yang diucapkan oleh empat tokoh utama. Melalui temuan analisis, terdapat 30 ujaran yang mengandung jenis kata slang. Dari empat jenis slang yang fresh and creative, compounding, imitative, acronim dan clipping, namun didalam film tersebut peneliti mendaptkan bahwa keempat karakter hanya menggunakan empat jenis slang, yaitu fresh and creative, compounding, imitative, dan clipping. Pada jenis slang, ditemukan bahwa karakter memiliki tujuan ketika menggunakan kata slang tersebut. Terungkap bahwa ada tiga fungsi slang, pursuit of self identity, emotive feeling of slang users, dan achieving politeness.Kata kunci: sosiolinguistik, variasi bahasa, kata-kata slang